Socialization of Black Cumin (Nigella Sativa) supplementation in Reducing Oxidative Damage Due to Covid-19 and Black Cumin Processing Training - Oktaviyanti, Ika Kustiyah; Nurrasyidah, Ira; Suhartono, Eko; Diani, Holly (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sungai Miai is a sub district located ini Banjarmasin Utara District, Banjarmasin, Kalimantan Selatan, Indonesia. The high activity of residents in services and trade and also many boarding houses for outsiders, may be one of the reasons why Sungai Miai in 2021 and 2022 received the title of 3rd sub-district with the highest number of Covid cases in Banjarmasin. The public does not yet know that Jintan Hitam can be used in the treatment of Covid 19. Jintan Hitam has been proven to repair oxidative damage from COVID 19. The solution we are trying to offer is increasing understanding of the benefits of Jintan Hitam and processing Jintan Hitam as a supplement that can repair oxidative damage from Covid 19. It is hoped that this training will encourage community members to be able to cultivate Jintan Hitam at home. There were 17 participants who attended with pretest results of 40 - 80 with an average of 65.29, while posttest results were 50 - 100 with an average of 81.17. The results show that there has been an increase in the knowledge of the Dasa Wasma of the Sungai Miai, Banjarmasin.